How Translators Play Language Games (and Win): Experimental Research - Ребрій, Олександр Володимирович; Пєшкова, Ольга Геннадіївна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2021)
The article is dedicated to experimental investigation of the specifics of reproducing nominative manifestations of language games in popular scientific discourse. We proceed from the understanding of language games by Ludwig Wittgenstein and Johan Huizinga according to which its varieties include acts of nomination and translation from one language into another. The material of the research is represented by quasi-terms – innovations of popular scientific discourse whose function is not only to give names to the objects of scientific reflection but also to provide context with expressive coloring (terminological connotation). At first, we applied the method of algorithmic modeling to formulate potential strategies for ascribing meaning to quasi-terms and reproducing them in Ukrainian, and afterwards we designed and conducted the retrospective experiment aimed at verifying the above psycholinguistic strategies. The experiment involved 34 semi-professional subjects, students for the Master’s Degree who conducted the translation of text fragments from popular scientific journals and submitted their reports in the form of the answers concerning the reproduction of control units (quasi-terms). The absence of standardized approach to resolving different types of translation difficulties together with a high level of linguistic competence determine the practicability of engaging semi-professionals in experimental investigation of translation strategies. The analysis of the experiment not only confirmed the validity of the modeled strategies but also allowed to describe the translators’ decisions in terms of the game theory. In particular, by attempting to coin the equivalent for a non-equivalent quasi-term on the basis of the model and word-building elements employed by the author (imitation or mirroring strategy) the translators follow the rules set by him/her, while by offering their own models and/or word-building elements the translators offer their own set own rules according to the circumstances of a new situation. In either case, the reproduction of a quasi-term in its lexicalized form can be seen as the translator’s victory, while omitting it in the target text is a clear sign of the translator’s defeat. Descriptive translation takes a somewhat intermediate position: on the one hand, it allows to convey the meaning of the source unit, but on the other hand, it leads to the loss of the source unit’s lexicalized form and concomitant terminological connotation.